2002
DOI: 10.1017/s0033291701004792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on the variation and covariation of attention deficit-hyperactivity disorder (ADHD) and oppositional-defiant disorder/conduct disorder (ODD/CD) symptomatologies across informant and occasion of measurement

Abstract: The findings indicate that it is unlikely that the co-morbidity between ADHD and ODD/CD is due to environmental influences that are independent of ADHD. Rather it is likely to be due to a shared genetic liability either operating directly, or indirectly through gene-environment correlations or interactions. The covariation between phenotypes across informants and time is governed by a common set of genes, but it seems that ODD/CD is also influenced by additional genetic factors. Developmentally, different form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
130
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 28 publications
22
130
1
5
Order By: Relevance
“…Some research evidence suggests heterogeneity at several levels: phenotypic [e. g., 16], neuropsychological [e. g., 150], psychophysiological [e. g., 7,23,125], and genetic [e. g., 107,175,186]. There may be multiple developmental pathways from aetiological factors to behavioural symptoms [151,152].…”
Section: Influences On Pathogenesismentioning
confidence: 99%
“…Some research evidence suggests heterogeneity at several levels: phenotypic [e. g., 16], neuropsychological [e. g., 150], psychophysiological [e. g., 7,23,125], and genetic [e. g., 107,175,186]. There may be multiple developmental pathways from aetiological factors to behavioural symptoms [151,152].…”
Section: Influences On Pathogenesismentioning
confidence: 99%
“…Teacher reports of ADHD have been shown to have greater phenotypic and genetic stability in the Attention deficit hyperactivity disorder phenotype A Thapar et al short term 28 as well as a stronger association with neurocognitive correlates 29 than parent reports. Moreover, twin studies of teacher reports have shown no evidence of rater contrast effects.…”
Section: Teacher Reportsmentioning
confidence: 99%
“…28,[68][69][70] However, there is some additional genetic contribution specific to symptoms at the later time point in longitudinal studies. 28,68 This suggests that susceptibility genes for ADHD may also influence its continuity over time but that there may be additional genetic modifier loci that specifically influence the presence of symptoms at later ages. So far there has been one published longitudinal study that found association of the DRD4 7 repeat allele with ADHD and ADHD persistence in boys aged 4 and 11 years.…”
Section: Persistence and Continuitymentioning
confidence: 99%
“…The syndromes occur separately but can be comorbid. Both genetic and environmental factors contribute to the expression of the single diagnosis and their aggregation in families with attention deficit (Thapar et al 2001;Nadder et al 2002) and antisocial disorders (Faraone et al 1995;Burt et al 2005). Yet it remains controversial, whether the co-occurrence of the disorders in individuals (e.g., ADHD þ CD) aggregates in families, and represents a separate heritable entity.…”
Section: Introductionmentioning
confidence: 99%